PENGARUH JOB AUTONOMY DAN KEPERCAYAAN PADA PIMPINAN TERHADAP PERILAKU KERJA INOVATIF MELALUI EFIKASI DIRI SEBAGAI VARIABEL MODERASI PADA BADAN PERTANAHAN NASIONAL - Lubis, Anggikha Rizki; Junita, Audia; Asriadi, Azis (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of job autonomy and trust in leadership on innovative work behavior, to determine whether self-efficacy moderates the effect of job autonomy on innovative work behavior, to determine whether self-efficacy moderates the effect of trust in leadership on innovative work behavior at the National Land Agency. The number of samples in this study was 122 respondents. The analysis technique used was MRA. The results of the study indicate that job autonomy and trust in leadership have a positive and significant effect on innovative work behavior, self-efficacy does not moderate the effect of job autonomy on self-behavior and self-efficacy does not moderate the effect of trust in leadership on innovative work behavior at the National Land Agency.